Antioxidant activity and in vitro cytotoxicity study of the phenolic compounds from Piper sarmentosum - Ghazali, Nor Farahiyah; Mustafa, Farah Farisha; Tengku Muhammad, Tengku Sifzizul; Ibrahim, Maizatul Akma (2018)
Cancer is by far one of the most worrying health issues that continues to be the major killing diseases worldwide, accounting for more than 6 million deaths. It is predicted that cancer incidence is continue rising every year with an approximated 12 million of deaths by 2030. In the confrontation of advances in modern medicine such as surgery, chemotherapy, radiotherapy and hormone therapy, cancer disease persists a worldwide problem. Thus the search for excellent anticancer agents avertable to human malignancies is needed from the nature. The winnowing of natural products notably plant extracts in few exceptional clinically active plant products such as vinca alkaloids and podophyllotoxin derivatives. Since the past few years, the search for new alternatives has been concentrated in finding medicinal herbs from local natural resources. In fact, about 60% of currently applied cancer drugs are derived from natural sources, due to its fewer side effects. Piper sarmentosum Roxb. which is locally known as ‘kaduk’, is one of natural medicinal plant that had been used traditionally to treat headache, arthritis, menstrual pain, cough and eczema. It is proven to have various biological properties such as anti-inflammatory, antioxidant, antimalarial, antiplasmodial, anti-diabetic, antifungal and anticarcinogenic. The aims of this study were to identify the phenolic compounds of P. sarmentosum methanolic extracts by measuring total phenolic content, and HPLC analysis. The antioxidant activity was also evaluated by DPPH scavenging assay. MTS assay was also conducted to study the effect of the extracts on human breast cancer cells. The HPLC analysis showed the presence of quercetin, naringin, gallic acid and tannic acid in P. sarmentosum. P. sarmentosum exhibited antioxidant property at 96.98 ± 2.29 μg/mL by DPPH scavenging activity with its high phenolic content at 89.22 mg GAE/ g dry extract. The cytotoxicity screening of P. sarmentosum extract using MTS assay provided IC50 of 24.63 ± 0.23 μg/mL and 2.85 ± 0.16 μg/mL on MCF-7 and T-47D, respectively. In conclusion, the phenolic compounds obtained from P. sarmentosum possess potent antioxidant and anticancer activity against the tested breast cancer cells. Further study might focus on the compounds action mechanisms toward the cancerous cells.